A Lady with Systemic Lupus Erythematosus and Mitral Stenosis - Alam, Muhammad Badrul; Hoque, Sania; Khan, Amiruzzaman; Hossain, Md Zakir; Asaduzzaman, Khondoker (Bangladesh Heart Journal, 2017)
Mitral stenosisis a valvular heart disease caused by a number of diseases. Chronic rheumatic fever is the most important cause. Among rare causes, some rheumatoid diseases like SLE may involve cardiovascular system causing libman- sacks endocarditis,pericardial diseases and other valvular lesions mostly associated with positive antiphospholipid and anticardiolipin antibody.Here, we presented a case of rheumatic mitral valvular heart disease having systemic lupus erythromatosus but negative antiphospholipid and anticardiolipin antibody. Bangladesh Heart Journal 2016; 31(2) : 109-112